The impact of ERP system implementation on the development of modern economic flows in the company - Živković, Marijana; Maričić, Srđan (Ekonomija - teorija i praksa, 2023)
The accelerated development of information and communication technologies (ICT), from the end of the 20th century until today, has made a great contribution to all segments of social life, and a significant part of this contribution is the impact on modern economic trends. New forms of business, such as digital marketing, electronic banking, and the web market, have confirmed old and set new theoretical postulates in economic science as well, although there are still disagreements at the global level regarding the intertwining of the understanding of traditional economic flows and terms with newly introduced economic flows and terms. ERP (Enterprise Resource Planning) basically represents a business information system, i.e., a set of commercial software packages for small, medium, and large companies.The subject of research in this paper is the analysis of the ERP system project in JKP Gradska čistoća in Belgrade, done with the aim of encompassing and describing the company’s business processes, identifying problems and proposing a solution with other information important for further steps.The goal of the research work is the analysis of business processes, implemented software, and possible suggestions for improvement through the implementation of new technologies and solutions and integration between different systems, which would eliminate problems that complicate the development of business processes and reduce the efficiency of the organization.Basic hypothesis of the work: The implementation of the ERP system has a significant impact on the development of modern economic flows in a company such as PUK Gradska čistoća in Belgrade. Research methodology and main results: The project included business processes and areas for which the ERP system can be responsible: operational, landfill and recycling, legal personnel affairs, economic sector, commercial sector, maintenance, and level of the enterprise and other services in the enterprise. During the research, the authors used analysis and synthesis methods, classification methods, comparison methods, and statistical methods. The main research results of this work are presented in the chapter "Research Results".